Impact of depopulation of municipalities in the Świętokrzyskie voivodeship on green infrastructure changes - Dziekański, Paweł (Wpływ depopulacji gmin województwa świętokrzyskiego na zmiany zielonej infrastruktury, 2025)
Background: Depopulation leads to changes in green spaces and quality of life, but can also provide opportunities for spatial regeneration. Green infrastructure is crucial for sustainable development, public health, and adaptation to climate change. Aim: The aim was to analyse and evaluate the relationship between depopulation in municipalities in the Świętokrzyskie voivodeship and the development of green infrastructure in a resource-constrained environment. The study focused on the impact of depopulation on the quality of green infrastructure. Methodology: The study used literature analysis, statistical methods, and TOPSIS, collecting empirical data from municipalities in the Świętokrzyskie voivodeship in 2014 and 2022, which allowed to capture the dynamics of the phenomena and monitor conjunctural changes. Results: The study of the impact of depopulation on green infrastructure in municipalities of the Świętokrzyskie voivodeship showed positive changes in the quality of green spaces, promotion of sustainable development, revitalisation of urban spaces, and the creation of new green spaces in response to demographic changes. Implications and recommendations: It is recommended to continue investing in green infrastructure, especially in areas with its lower concentration and to monitor changes in green space distribution and demographics. Originality/value: The author analysed the relationship between demographic structure and green infrastructure in municipalities, using a synthetic measure for both areas to compare 2014 and 2022, allowing an assessment of their impact on the environment, the depopulation process, and infrastructure.
Biblioteka Regionalisty = Regional Journal, 2025, Nr 25, s. 48-61
Keywords: green infrastructure; demographics; synthetic measure; CRITIC-TOPSIS method; zielona infrastruktura; demografia; miara syntetyczna; metoda CRITIC-TOPSIS